Design of Betel Nut Peeler Machine Based on Quality Function Deployment and Value Engineering - Yunus Pardosi; Anita Susilawati (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2023)
The goal of this study is to design a betel nut peeler machine based the Quality Function Deployment (QFD) and Value Engineering methods to optimize the stripping of betel nut process. A case study was carried out in the Keritang District of the Tembilahan Regency of Riau Province, Indonesia. Previously, the Keritang District community used the manual processes stripping technique, thus the final production cannot be in huge amounts. The method was implemented through several steps that began with gathering data and information about the machines desired by the community using QFD and Value Engineering. The machine was designed with the goals of being simple to use, efficient, and responsive to the needs of the community in mind. Each of these characteristics is discussed in the House of Quality. As a result, the Value Engineering approach was developed to uncover effective costs to deliver good quality, appearance, or features, and it may be used to improve product quality, lower costs, boost efficiency, and reduce risk. Finally, an appropriate and optimal design for the betel nut peeler was developed. The benefit of betel nut peeler machine design is supposed to be simple to use and to provide big amounts of stripping results quickly. As a result, the production of betel nut peeling rises.